Disentangling the Time-Frequency Nexus of Oil, Uncertainties, and Saudi Equities: A Wavelet Local Multiple Correlation Approach - Hamida, Hela Ben; Aloui, Chaker (International Journal of Energy Economics and Policy, 2025)
This paper examines the combined and separate effects of geopolitical risk, economic policy uncertainty, and oil prices on the stock market within a multivariate time-frequency framework, focusing on Saudi Arabia as an oil-rich country. We implement the wavelet local multiple correlation approach using monthly data from January 2000 to December 2024. Our results reveal that oil prices, geopolitical risk, and economic uncertainty are key drivers of Saudi market behavior. The joint and individual effects vary significantly across time scales and frequencies. Increasing uncertainty surrounding economic policies and rising geopolitical tensions in the region have intensified the impact of oil price movements on the Saudi market. These findings have several implications for portfolio managers, foreign investors, and policymakers. When analyzing and forecasting stock returns, portfolio managers should consider oil prices, geopolitical risk, and changes in economic policy uncertainty.